Peran Lembaga Konsultasi Dalam Merubah Sikap dan Persepsi Isteri Korban Dampak KDRT di Sambas Perspektif Hukum Islam dan Hukum Positif - Sri sudono saliro Ridho Anugrah Nurhasanah (Raheema, 2022)
Legal Aid and Consultation Agencies â€œSambasâ€ is a means and act of the victim is a central attitude. Without an attitude as a function of encouraging victims' actions, the consultative body cannot run effectively. The focus of this research is related to how the role of the consulting agency in changing the attitudes and perceptions of the wives of victims of the impact of domestic violence, research place in Sambas. This study is: empirical research with a starting point on a descriptive analytical approach, to get the data, researchers took steps to observe and interview. The findings of the study are: the attitude of the wife of the victim of domestic violence always closes because the act is a disgrace to the family and perceives the perpetrator's actions are simply a mistake. Therefore the role of LKBH Sambas is very important in gathering information from victims related to the facts of the field through communicative and persuasive approaches, as well as the value of benefits contained in the qurâ€™an. Keywords: Role of Consultation Institutions, Attitudes and Perceptions, Impact of Domestic Violence, Sambas